2014
DOI: 10.2337/db14-0393
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Supports the Antidiabetic Effect of a Sodium Glucose Cotransporter 2 Inhibitor by Suppressing Endogenous Glucose Production in Diabetic Mice

Abstract: Combined use of metformin and a sodium glucose cotransporter 2 inhibitor (SGLT2I) is a promising treatment strategy for type 2 diabetes. The mechanism by which combination treatment provides better glycemic control than metformin or SGLT2I monotherapy remains elusive. Therefore, we investigated the physiological mechanism by which both compounds lower blood glucose concentrations in diabetic mice. We compared the potential of metformin and the SGLT2I AVE2268 alone or in combination to mitigate hyperglycemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…39,40 Several attempts have been made to overcome peripheral insulin resistance by amplifying insulin output. 37 In this study, these findings have demonstrated that UDCA and 4-PBA ameliorated insulin resistance, and 4-PBA improved glucose tolerance in a diabetic db/db murine model.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…39,40 Several attempts have been made to overcome peripheral insulin resistance by amplifying insulin output. 37 In this study, these findings have demonstrated that UDCA and 4-PBA ameliorated insulin resistance, and 4-PBA improved glucose tolerance in a diabetic db/db murine model.…”
Section: Discussionmentioning
confidence: 55%
“…Unrestrained endogenous glucose generation may contribute to fasting hyperglycemia, which is usually accompanied with peripheral insulin resistance and/or inadequate insulin release. 37 Recently, podocytes, the key component of the glomerular filtration barrier, were found to be uniquely insulin sensitive in some manner, and they were able to take up glucose via the translocation of glucose transporters GLUT1 and GLUT4. 38 In an insulin resistance state, the impaired capacity of glucose uptake for podocytes has been shown to provoke kidney dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent clinical and preclinical advances highlight that parallel targeting of more than one biological mechanism yields superior metabolic efficacy and fewer adverse events compared to traditional monotherapies (Sadry and Drucker 2013). Simultaneous targeting of multiple metabolic pathways can be achieved by coadministration of two distinct hormones (Cegla et al 2014;Fonseca et al 2010;Morrow et al 2011;Muller et al 2012;Neschen et al 2015) or through the application of unimolecular polyagonists. These multifunctional hormones combine to embellish certain hormone action profiles but, more importantly, serve to recruit distinct pharmacology that leads to enhanced efficacy and safety (Day et al 2009;Finan et al 2012Finan et al , 2013Finan et al , 2015Pocai et al 2009;Schwenk et al 2014).…”
Section: Multi-hormone Combination Therapiesmentioning
confidence: 99%
“…In addition, SGLT-2 inhibitors are associated with a rise in fasting plasma glucagon concentrations and endogenous glucose production, which could limit efficacy 108,109. However, preclinical studies have shown the suppressive effects of metformin on HGP to counteract the rise in endogenous glucose production and thereby enhance the glucose-lowering properties of SGLT-2 inhibitors 110. DPP-4 inhibitors, which suppress glucagon secretion and therefore inhibit endogenous glucose production,111 have been shown to reduce SGLT-2 inhibitor-induced increases in glucagon when used concomitantly 112…”
Section: Triple Oral Combination Therapymentioning
confidence: 99%